Longshore Sediment Transport on the Brazilian Continental Shelf - Beloti Trombetta, Thaísa; Correa Marques, Wiliam; Cardoso Guimarães, Ricardo; de Paula Kirinus, Eduardo; Vieira da Silva, Douglas; Oleinik, Phelype Haron; Fagundes Leal, Thalita; Isoldi, Liércio André (Scientia Plena, 2019)
Beaches are suffering morphological changes due the interaction between energetics components and local sedimentary supply imbalance. The understanding of the wave climate is an essential source of information for the composition of coastal planning projects. The main goal of this work is to estimate the longshore sediment transport (LST) in various sectors of the Brazilian Coast, and to identify the annual average and its dominant direction. For this study was considered the period between 1979 and 2015, applying computational modeling to investigate the waves behavior, and empirical formulas to calculate LST rates. The results showed a great discrepancy in the wave climate along the Brazilian Coast, and presented similarities rates between the estimation of LST and previous studies for different sectors analyzed. The sector where transport rates have been higher understanding the Northeast region, specifically between Alagoas and Rio Grande do Norte states. The opposite of it was observed in the Southern part of Bahia. The dominant direction of sediments, mainly caused by the waves, was directed to South between Rio de Janeiro and Bahia states, and in some parts of Sergipe. Transportation to the north comprises the South and Southeast regions, as well as a considerable area of the Northeast and the entire Northern Region. In this sense, information related to wave behavior and sediment transport along the Brazilian Coast is presented, unlike studies available in the literature that are carried out locally and approach only specific regions. Thus, the results presented can be considered in future projects, involving the sustainable management of coastal zones.